Global prevalence of chronic kidney disease: A systematic review and meta-analysis - Hill, N; Fatoba, S; Oke, J; Hirst, J; O'callaghan, C; Lasserson, D; Hobbs, F (Public Library of Science, 2016)
Chronic kidney disease (CKD) is a global health burden with a high economic cost to health systems and is an independent risk factor for cardiovascular disease (CVD). All stages of CKD are associated with increased risks of cardiovascular morbidity, premature mortality, and/or decreased quality of life. CKD is usually asymptomatic until later stages and accurate prevalence data are lacking. Thus we sought to determine the prevalence of CKD globally, by stage, geographical location, gender and age. A systematic review and meta-analysis of observational studies estimating CKD prevalence in general populations was conducted through literature searches in 8 databases. We assessed pooled data using a random effects model. Of 5,842 potential articles, 100 studies of diverse quality were included, comprising 6,908,440 patients. Global mean(95%CI) CKD prevalence of 5 stages 13·4%(11·7-15·1%), and stages 3–5 was 10·6%(9·2-12·2%). Weighting by study quality did not affect prevalence estimates. CKD prevalence by stage was Stage-1 (eGFR>90+ACR>30): 3·5% (2·8-4·2%); Stage-2 (eGFR 60-89+ACR>30): 3·9% (2·7-5·3%); Stage-3 (eGFR 30-59): 7·6% (6·4-8·9%); Stage-4=(eGFR 29-15): 0·4% (0·3-0·5%); and Stage-5 (eGFR<15): 0·1% (0·1-0·1%). CKD has a high global prevalence with a consistent estimated global CKD prevalence of between 11 to 13% with the majority stage 3. Future research should evaluate intervention strategies deliverable at scale to delay the progression of CKD and improve CVD outcomes.